Proprietary methodology of sociological text analysis - Tsarkov, Petr E. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This article considers experience of applying such sociological methods as content analysis and information-goal analysis to studying the heritage of representatives of pre-revolution Russian social conception (P. I. Novgorodtsev, B. P. Vysheslavtsev, I. A. Ilyin and N. N. Alekseev). The author applies methodological model of semantic and structural analysis based on combination of classical qualitative and quantitative content analysis and information-goal analysis.